Masculinity against the grain in Damon Galgut's The beautiful screaming of pigs, André Carl van Merwe's Moffie and Koos Prinsloo's Jonkmanskas. (1st September 2016) - Mason, Paul
ABSTRACT: This article pays attention to strains of resistance to conscription and its bedrock ideology of masculinity in texts written by gay authors who performed their National Service, each of whose protagonists narrate their experiences as conscripts. The texts discussed, in order of analysis, are two novels written during the post-apartheid period in the form of Damon Galgut's The beautiful screaming of pigs (1991, revised edition 2006) and André Carl van der Merwe's Moffie (2006), followed by a collection of short stories written during the final decade of apartheid rule – Koos Prinsloo's Jonkmanskas (1982). Emphasis is placed on fictional representations of the tensions at work between the privately felt identity of a gay young man and the publicly sanctioned notions of what it meant to be a man within the context of the military life and the wider social context. Having examined gay experiences and struggles for identity as expressed in the novels of Galgut and Van der Merwe, the article concludes by arguing that the short stories of Prinsloo provide a gay political agenda that distinguishes it from the work of the two novelists.